1982
DOI: 10.1111/j.1471-4159.1982.tb08684.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid:Coenzyme A Ligase in Brain: Fatty Acid Specificity in Cellular and Subcellular Fractions

Abstract: We measured long-chain fatty acid: coenzyme A (CoA) ligase (EC 6.2.1.3) activity with four fatty acids in brain homogenates, and cellular and subcellular fractions to determine whether there are differences in activity that could be correlated with differences in fatty acid composition and metabolism. In rat brain homogenates, ligase activity varied appreciably with the four acids, with 18:2 greater than 18:1 greater than 16:0 greater than 22:1 (nmol acyl-CoA formed/min/mg protein: 1.46, 1.20, 0.96, and 0.57, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…The trend is similar to the rates of activation seen with the 18-carbon substrates (table 3). When one considers the chain-elongated homologues of the 18-carbon compounds the order of activation was dihomo-cu-linolenic> dihomo-y-linolenic> dihomolinoleic> arachidoleic>arachidic (10.62, 10.31, 10.15, 9.83, 9.17 Table 3 Comparison of the maximal rates of activation of all the 18-carbon fatty acids with the long-chain acyl: CoA synthetase of human erythrocyte ghosts relative to C18:O (stearic acid) The erythrocyte exhibited activity similar to that of organelles investigated by other workers [19], and second only to that of the hepatocyte (Davidson and Cantrill, unpublished), and, of course, erythrocyte ghosts being plasma membrane only, this activity was directly attributable to such membranes. Morand and Aigrot [20] have recently shown that erythrocyte ghosts resealed with ATP and CoASH inside exhibited palmitoyl : CoA synthetase activity.…”
Section: Resultsmentioning
confidence: 69%
“…The trend is similar to the rates of activation seen with the 18-carbon substrates (table 3). When one considers the chain-elongated homologues of the 18-carbon compounds the order of activation was dihomo-cu-linolenic> dihomo-y-linolenic> dihomolinoleic> arachidoleic>arachidic (10.62, 10.31, 10.15, 9.83, 9.17 Table 3 Comparison of the maximal rates of activation of all the 18-carbon fatty acids with the long-chain acyl: CoA synthetase of human erythrocyte ghosts relative to C18:O (stearic acid) The erythrocyte exhibited activity similar to that of organelles investigated by other workers [19], and second only to that of the hepatocyte (Davidson and Cantrill, unpublished), and, of course, erythrocyte ghosts being plasma membrane only, this activity was directly attributable to such membranes. Morand and Aigrot [20] have recently shown that erythrocyte ghosts resealed with ATP and CoASH inside exhibited palmitoyl : CoA synthetase activity.…”
Section: Resultsmentioning
confidence: 69%
“…It is possible that fatty acid hydroperoxides form, through the action of ligase, complexes with CoA, thereby slowing the rate of activation of arachidonate. Long-chain fatty acid ligases have been shown to be relatively unspecific enzymes (Murphy and Spence, 1982). In the absence of added lysophospholipids, the incorporation of [ 1 -'4C]arachidonate is limited by the supply of endogenous substrate generated by phospholipases.…”
Section: Discussionmentioning
confidence: 99%
“…At 45 "C both myelin and microsomes This study has demonstrated that long-chain acylCoA synthetase, an enzyme well characterized in brain and shown to be localized in microsomes as well as other subcellular fractions [Vignais et al, 1958;Pande and Meade, 1968;Cantrill and Carey, 1975;Fisher and Rowe, 1980;Murphy and Spence, 1982;Brophy and Vance, 1982;Bazan, 1983, 1985a,b], also occurs at an appreciable level in rat brain myelin. The fact that highly purified myelin contained as much as 11-15% of the activity in microsomes tended to rule out contamination by the latter as the source of activity.…”
Section: Resultsmentioning
confidence: 93%